Sustainable livelihood through high-value Kadaknath poultry farming - Mooventhan, P; Kumar, Jagdish; Dixit, Anil; Sharma, K C; Sivalingam, P N; Gupta, Amit Kumar; Singh, Uttam; Singh, S R K; Venkatesan, P; Kaushal, Pankaj (Indian Farming, 2019)
Kadaknath poultry was recommended to the native farmers of Kasdol block under the Farmer FIRST Programme. Around 6,000 Kadaknath chicks were procured and provided to 120 farm families. Fifty Kadaknath chicks (25-30 days old) were provided to each beneficiary. Various capacity building programmes regarding the scientific methods of production, vaccination schedule and marketing were provided. Steps were also taken to train the beneficiaries in the management of hatchery units. Farmers were highly benefitted through the project by earning considerable income and became financially stable.